Scientific School of Accounting and Audit at the Rostov State University of Economics (RINH) - N. T. Labyntsev (Учёт. Анализ. Аудит)
The article provides a concise overview of the activities of the scientifi school at the Accounting Department of the Russian State Economic University (RSUE) during the period 2023–2024. The main areas of scientific work are discussed, including research conducted on contractual topics and publication output. Monographs have been produced, articles published in peer-reviewed scientifi journals, and abstracts presented at scientifi and practical conferences. The faculty of the department plays a significant role in the development of the scientific school. They actively participate in scientific publications, image events at various levels, and maintain creative ties with universities across the Russian Federation and partner organizations of the university. The scientifi school and its representatives have received widespread recognition from the Rector’s Office, government, and public organizations.